Phenotypic stability of yellow melon hybrids evaluated in the Agricultural Pole Mossoró-Assu - Nunes, Glauber Henrique de Sousa; Madeiros, Antônio Edilberto de Sousa; Grangeiro, Leilson Costa; Santos, Gilmara Mabel; Sales Júnior, Rui (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to estimate the participation of single and complex components of interaction as well as to identify cultivars with high phenotypic adaptability and stability. Twelve hybrids of yellow melon were evaluated in four sites of Rio Grande do Norte in 2000, 2001, 2002 coming to twelve environments. The experiments were carried out in a randomized complete block design with three replications. The experimental plot was constituted by two 5 m long rows. Yield and total soluble solids contents were evaluated. For the partition of the hybrids by environments interaction in single and complex part, the method of Cruz and Castoldi was used. In order to indentify hybrids with high phenotypic adaptability and stability, the Toler method was utilized. Great variation among environments and hybrids as well as interaction were observed between these two factors. The complex part is responsible for most of the environment hybrids interaction. Hybrids AMR-04 and AMR-12, comprising higher means to yield and total soluble solids content, are responsive to the improved environment.